2017
DOI: 10.1093/nar/gkx610
|View full text |Cite
|
Sign up to set email alerts
|

PhiReX: a programmable and red light-regulated protein expression switch for yeast

Abstract: Highly regulated induction systems enabling dose-dependent and reversible fine-tuning of protein expression output are beneficial for engineering complex biosynthetic pathways. To address this, we developed PhiReX, a novel red/far-red light-regulated protein expression system for use in Saccharomyces cerevisiae. PhiReX is based on the combination of a customizable synTALE DNA-binding domain, the VP64 activation domain and the light-sensitive dimerization of the photoreceptor PhyB and its interacting partner PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…The first optogenetic switch developed and implemented in yeast was based on the red-light dependent interactions of the photoreceptor Phytochrome B (PhyB) and its interacting protein PIF3 from Arabidopsis thaliana (6). Ever since, this switch has been adapted in yeast with different purposes such as: reconstitution of protein activities (7), subcellular protein localization, control of cell polarity and budding phenotypes (33, 34), and reporter gene expression (YFP or GFP) (19, 35). Recently, a new red-light optogenetic switch also based on PhyB-PIF3 interaction (named PhiReX), that overcomes the obstacle of external addition of the chromophore phycocyanobilin (PCB), has been implemented and tested in yeast (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first optogenetic switch developed and implemented in yeast was based on the red-light dependent interactions of the photoreceptor Phytochrome B (PhyB) and its interacting protein PIF3 from Arabidopsis thaliana (6). Ever since, this switch has been adapted in yeast with different purposes such as: reconstitution of protein activities (7), subcellular protein localization, control of cell polarity and budding phenotypes (33, 34), and reporter gene expression (YFP or GFP) (19, 35). Recently, a new red-light optogenetic switch also based on PhyB-PIF3 interaction (named PhiReX), that overcomes the obstacle of external addition of the chromophore phycocyanobilin (PCB), has been implemented and tested in yeast (35).…”
Section: Discussionmentioning
confidence: 99%
“…Ever since, this switch has been adapted in yeast with different purposes such as: reconstitution of protein activities (7), subcellular protein localization, control of cell polarity and budding phenotypes (33, 34), and reporter gene expression (YFP or GFP) (19, 35). Recently, a new red-light optogenetic switch also based on PhyB-PIF3 interaction (named PhiReX), that overcomes the obstacle of external addition of the chromophore phycocyanobilin (PCB), has been implemented and tested in yeast (35). These types of toggle switches can be quite powerful as they provide activation with a given wavelength (red) to then be turned off by another one (far-red).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on TALE-based hybrids applied in human and yeast cells also reported background activity of TALE-based two-component systems in the absence of inducing signals (light or ligand; Konermann et al, 2013;Hochrein et al, 2017). This problem was circumvented by the fusion of nuclear export signals to the BC, which should prevent its nuclear import in the absence of interaction with the AC.…”
Section: N-terminal Truncations Reduce Background Activity Of the Bcmentioning
confidence: 99%
“…This problem was circumvented by the fusion of nuclear export signals to the BC, which should prevent its nuclear import in the absence of interaction with the AC. TALEreconstitution in the cytoplasm then triggers piggyback nuclear import of the BC mediated by the NLS present in the AC (Konermann et al, 2013;Hochrein et al, 2017). We followed different strategies to reduce the background activity and focused initially on the BC alone.…”
Section: N-terminal Truncations Reduce Background Activity Of the Bcmentioning
confidence: 99%
See 1 more Smart Citation